2019
DOI: 10.1177/0957650919878313
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the effect of complex impeller on vibration characteristics for a high-speed centrifugal pump

Abstract: In this article, to improve the vibration characteristics of a high-speed centrifugal pump, two new types of complex impeller were designed for replacing the original long-blade impeller. The experimental apparatus of pump vibration was designed and used to test the vibration signals of the model pump with the original impeller in frequency field. The vibration amplitude of 0.12 mm/s2 is observed on the shaft rotating frequency, while the amplitudes of 0.04 mm/s2, 0.14 mm/s2, and 0.2 mm/s2 respectively on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…e impeller is the core part of the centrifugal pump, and the impeller blade profile plays a vital role in the fluid flow which will directly impact the performance of centrifugal pumps. At present, there have been many studies on the influence of the impeller parameters on the flow characteristics of centrifugal pumps [11][12][13][14][15][16][17][18][19][20]. Tao et al [21] used the numerical method to study how the blade thickness influenced the flow characteristics in the impeller passages and volute casing.…”
Section: Introductionmentioning
confidence: 99%
“…e impeller is the core part of the centrifugal pump, and the impeller blade profile plays a vital role in the fluid flow which will directly impact the performance of centrifugal pumps. At present, there have been many studies on the influence of the impeller parameters on the flow characteristics of centrifugal pumps [11][12][13][14][15][16][17][18][19][20]. Tao et al [21] used the numerical method to study how the blade thickness influenced the flow characteristics in the impeller passages and volute casing.…”
Section: Introductionmentioning
confidence: 99%
“…The design of the centrifugal pump is generally based on the uniform inflow. The velocity of each fluid particle in the inlet section of the impeller is approximately the average velocity on the flow surface, while the direction is perpendicular to the outlet section of the suction chamber [7][8][9]. Under this ideal environment, the blade design makes the impeller achieve the best work.…”
Section: Introductionmentioning
confidence: 99%
“…In the optimization of centrifugal pumps, adding splitter blades is one of the most used optimization methods [2][3]. Yuan Y designed two impellers with different types of splitter blades for a high-speed centrifugal pump respectively, compared with the original impeller, the new impeller can not only improve the pump head but also reduce the vibration amplitude of the pump [4]. Mou J G concluded that under the condition that the design requirements were met, the impeller with long and short staggered blades has the best anti-cavitation performance [5].…”
Section: Introductionmentioning
confidence: 99%